The antibacterial and antibiofilm activity of Granudacyn in vitro in a 3D collagen wound infection model. (2nd November 2022) - Esin, Semih; Kaya, Esingül; Maisetta, Giuseppantonio; Romanelli, Marco; Batoni, Giovanna
Abstract : Objective: It is widely agreed that infection and the formation of biofilms play a major role in increasing inflammation and delaying wound healing. The aim of this study was to evaluate, in vitro, the antimicrobial activity of the wound irrigation solution, Granudacyn (Mölnlycke Health Care AB, Sweden) against planktonic bacteria and mature biofilms of clinically relevant bacterial species. Method: Quantitative evaluation of bacterial numbers and confocal and/or scanning electron microscopy were used to evaluate the wound irrigation solution's antimicrobial/antibiofilm activity in standard laboratory conditions as well as in a three-dimensional (3D) collagen wound infection model. Results: The wound irrigation solution exhibited a rapid and strong antibacterial activity against both Gram-positive and Gram-negative strains isolated from infected wounds in planktonic form, with a reduction in bacterial number of >4 Logs after as little as one minute of treatment. The wound irrigation solution also exerted an evident activity against preformed biofilms of Pseudomonas aeruginosa and Staphylococcus aureus (>3 Log and >1 Log reduction in colony forming unit number, respectively, after 15 minutes of incubation). Although the wound irrigation solution was partially inhibited in the presence of simulated wound fluid, it maintained a marked antibiofilm activity in in vivo-like conditions (ie. in a 3D collagen wound infection model) with a strong killing and a mild debridement effect, which was superior to standard saline. Conclusion: The results obtained in this study suggest that although the wound irrigation solution used might be partially inhibited by wound exudate, it has the potential to effectively kill wound infecting planktonic as well as biofilm bacteria.